EFFECT OF TOTAL QUALITY MANAGEMENT ON THE PERFORMANCE OF FEDERAL ROAD SAFETY CORPS, ABUJA - Kamal, Musa; Nanzing Dannap, Edmond; Dogara Gado, Nuhu (African Journal of Social and Behavioural Sciences, 2026)
The ever-improving global competition and increasing requests for more qualified products by customers have caused organisations to understand that the only way to survive in the market is to deliver better quality products to meet customers’ needs. Therefore, the study examined the effect of total quality management on the performance of the Federal Road Safety Corps, Abuja. The study adopted a descriptive research design, using survey method. The entire population of 594 officers and men of the Abuja Federal Road Safety Corps were used for the study. The data was collected using a questionnaire and was analysed using correlation and regression techniques. The results of the analysis revealed that TQM has a significant and positive effect on the performance of FRSC, Abuja. Specifically, TQM components such as top management commitment and employee involvement showed a significant positive effect on performance. The study therefore recommended that the FRSC should channel more effort toward getting top management to be committed to quality and also involve men and officers in the quality process.